PERANCANGAN USER INTERFACE PADA START-UP KESEHATAN HEALTHY MENGGUNAKAN METODE DESIGN THINKING - Mahasinul Akhlak, Muhammad Lutfi; Nastiti, Tri Mufidah; Fatullah, Rezqy; PU, Guntur Bintang (STMIK BINA PATRIA, 2023)
Health is everyone's priority. When a person experiences health problems, the best effort will be made by the patient and his family. Because complete information about health services, medicines and supporting medical devices is crucial and most sought after. Healthy digital start-ups are designed to find solutions and bridge these difficulties by connecting Pharmacy partners and Medical Device Stores who are able to provide BPOM-certified legal drug products and quality medical devices with users, in this case patients and their families. In this study, the method used was